Balancing Bulkiness in Gold(I) Phosphino‐triazole Catalysis. Issue 31 (30th July 2019) - Zhao, Yiming; Wakeling, Matthew G.; Meloni, Fernanda; Sum, Tze Jing; van Nguyen, Huy; Buckley, Benjamin R.; Davies, Paul W.; Fossey, John S.
Abstract : The syntheses of a series of 1‐phenyl‐5‐phosphino 1, 2, 3‐triazoles are disclosed, within which, the phosphorus atom (at the 5‐position of a triazole) is appended by one, two or three triazole motifs, and the valency of the phosphorus(III) atom is completed by two, one or zero ancillary (phenyl or cyclohexyl) groups respectively. This series of phosphines was compared with tricyclohexylphosphine and triphenylphosphine to study the effect of increasing the number of triazoles appended to the central phosphorus atom from zero to three triazoles. Gold(I) chloride complexes of the synthesised ligands were prepared and analysed by techniques including single‐crystal X‐ray diffraction structure determination. Gold(I) complexes were also prepared from 1‐(2, 6‐dimethoxy)‐phenyl‐5‐dicyclohexyl‐phosphino 1, 2, 3‐triazole and 1‐(2, 6‐dimethoxy)‐phenyl‐5‐diphenyl‐phosphino 1, 2, 3‐triazole ligands. The crystal structures thus obtained were examined using the SambVca (2.0) web tool and percentage buried volumes determined. The effectiveness of these gold(I) chloride complexes to serve as precatalysts for alkyne hydration were assessed. Furthermore, the regioselectivity of hydration of but‐1‐yne‐1, 4‐diyldibenzene was probed. Abstract : The synthesis of gold(I) complexes of 1‐phenyl‐5‐phosphino 1, 2, 3‐triazoles with varying numbers of triazole units appended to phosphorus are disclosed and compared to tricyclohexylphosphine and triphenylphosphine. The gold(I) chloride complexes synthesised were analysed by techniques including single‐crystal X‐ray diffraction structure determination and percentage buried volumes thereof determined. These complexes were compared as catalyst precursors for gold(I)‐mediated alkyne hydration and the corresponding results surveyed with respect to the bulkiness of the ligands deployed.